Finger Print Based Door Locking System (International Journal of Engineering and Computer Science, 2017)
Security has been playing a key role in many of our places like offices, institutions, libraries, laboratories etc. in order to keep our data confidentially so that no other unauthorized person could have an access on them. Nowadays, at every point of time, we need security systems for protection of valuable data and even money. This paper presents a fingerprint based door opening system which provides security which can be used for many banks, institutes and various organizations etc..,. There are other methods of verifying authentication through password, RFID but this method is most efficient and reliable. To provide perfect security to the bank lockers and to make the work easier, this project is taking help of two different technologies viz. EMBEDDED SYSTEMS and BIOMETRICS. Unauthorized access is prohibited by designing a lock that stores the fingerprints of one or more authorized users. Fingerprint is sensed by sensor and is validated for authentication. If the fingerprint matches, the door will be opened automatically otherwise the buzzer connected to an audio amplifier will be activated so that the people near the surroundings will get an alert.